2015
DOI: 10.1902/jop.2015.140664
|View full text |Cite
|
Sign up to set email alerts
|

β2‐Glycoprotein I‐Dependent Anti‐Cardiolipin Antibodies Associated With Periodontitis in Patients With Systemic Lupus Erythematosus

Abstract: Elevated anti-CL and anti-β2GPI antibody levels were associated with periodontopathic bacteria and periodontal breakdown in patients with SLE. Periodontitis might be a modifiable risk factor for SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 47 publications
0
31
1
3
Order By: Relevance
“…A review by Karnoutsos et al summarizes evidence that a peptide found i n β 2 G P I m a y a l s o b e f o u n d i n A c t i o b a c i l l u s actinomycetemcomitans and P. gingivalis [93]. Wang et al [94] reported that aPL were associated with periodontitis in patients with SLE and confirmed the presence of P. gingivalis and Treponema denticola in saliva and plaque samples of these patients, detected by PCR.…”
Section: Periodontal Infections Smoking and Aplmentioning
confidence: 99%
“…A review by Karnoutsos et al summarizes evidence that a peptide found i n β 2 G P I m a y a l s o b e f o u n d i n A c t i o b a c i l l u s actinomycetemcomitans and P. gingivalis [93]. Wang et al [94] reported that aPL were associated with periodontitis in patients with SLE and confirmed the presence of P. gingivalis and Treponema denticola in saliva and plaque samples of these patients, detected by PCR.…”
Section: Periodontal Infections Smoking and Aplmentioning
confidence: 99%
“…An environmental factor that modulates autoimmunity is the bidirectional crosstalk between the human host and microbiota, as reported for rheumatic diseases [18, 19]. However, few studies have addressed the relationship between SLE and the human microbiota [20, 21] or the periodontal condition in SLE patients [10, 16, 2227]. Moreover, the results have been conflicting, due in part to small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…Diferenças intra-grupo (na coluna) significantes na prevalência de Aa em comparação a espécies dos complexos amarelo, verde, laranja e vermelho; Diferenças intra-grupo (na coluna) significantes na prevalência de outras espécies em comparação aos complexos amarelo, verde e laranja; Diferenças intra-grupo (na coluna) significantes na prevalência de bactérias do complexo verde em comparação ao laranja Poucos estudos avaliaram uma possível associação entre LES e doença periodontal (WANG et al 2015;MUTLU et al, 1993;MEYER et al, 2000;NOVO et al 1999;RHODUS et al 1990;NOVO et al 1999;KOBAYASHI et al 2003;KOBAYASHI et al 2007;FABBRI et al 2014) , 2001;STAPLES et al, 1974;CHEN et al, 2004). A escolha pela análise exclusivamente de mulheres baseou-se em sua maior prevalência de LES quando comparado a homens, além das diferenças de manifestação da doença, sendo comumente mais graves em homens (TAN et al, 2012).…”
Section: Les-i [Média(95%ciunclassified
“…Apenas um estudo (WANG et al, 2015) É importante mencionar que a diferença dos resultados encontrados em relação a outras pesquisas pode ser também explicada por diferentes critérios de definição de doença periodontal encontrados na literatura (RHODUS et al 1990;NOVO et al 1999;KOBAYASHI et al 2003;KOBAYASHI et al 2007;FABBRI et al 2014). Nesse trabalho, foi utilizado protocolo de exame periodontal de boca toda, conforme sugerido por Eke et al ANNANE et al, 2004;STAPLES et al, 1974;CHEN et al, 2004;PRYOR;BOLOGNA;KAHL, 1996).…”
Section: Les-i [Média(95%ciunclassified
See 1 more Smart Citation